Cancer risk among adolescents and young adults living with HIV in South Africa: a national cohort study - Ruffieux, Yann; Dhokotera, Tafadzwa; Muchengeti, Mazvita; Bartels, Lina; Olago, Victor; Bohlius, Julia; Singh, Elvira; Egger, Matthias; Rohner, Eliane (My University, 2021)
Background: We studied the incidence of and risk factors for various types of cancers in adolescents and young adults living with HIV (AYALWH) in South Africa between 2004 and 2014. Methods: We included individuals aged 15 to 24 years from the South African HIV Cancer Match study, a large cohort resulting from a linkage between HIV-related laboratory measurements from the National Health Laboratory Services and records from the National Cancer Registry. We computed incidence rates for the most common cancers. We assessed associations between these cancers and sex, age, calendar year, and CD4 cell count using Cox models and adjusted hazard ratios (aHR). Findings: We included 782,454 AYALWH (89% female). Of those, 867 developed incident cancer including 429 who developed Kaposi sarcoma, 107 non-Hodgkin lymphoma, 48 Hodgkin lymphoma, 45 cervical cancer, and 32 leukaemia. Kaposi sarcoma was more common in the 20-24 year age group than the 15-19 year age group (aHR 1.39, 95% CI 1.03-1.86). Male sex was associated with higher rates of Kaposi sarcoma (aHR 2.06, 95% CI 1.61-2.63), non-Hodgkin lymphoma (aHR 3.17, 95% CI 2.06-4.89), Hodgkin lymphoma (aHR 4.83, 95% 2.61-8.93), and leukaemia (aHR 5.90, 95% CI 2.87-12.1). Lower CD4 cell counts at baseline were associated with higher rates of Kaposi sarcoma, cervical cancer, non-Hodgkin and Hodgkin lymphoma. Interpretation: Infection-related cancers are the most common cancer types among AYALWH in South Africa. The burden of these cancers may be reduced through HPV vaccination, targeted HIV testing, early initiation of antiretroviral therapy, and improvement of treatment adherence.
Supplemental Materials: https://osf.io/rqzjd/
Keywords: adolescents; cancer; HIV; South Africa; young adults